2010
DOI: 10.1002/kin.20522
|View full text |Cite
|
Sign up to set email alerts
|

A new semiempirical kinetic method for the determination of ion exchange constants for counterions of cationic micelles: Study of the rate of pH‐independent hydrolysis of phthalimide as the kinetic probe

Abstract: Pseudo-first-order rate constants (k obs ) for pH-independent hydrolysis of phthalimide (1), obtained at a constant total concentration of cetyltrimethylammonium bromide and hydroxide ([CTABr] T ), 2.0×10 −4 M 1, 0.02 M MOH (M + = Li + , Na + and K + ) and various concentrations of inert salt MX (= LiCl, LiBr, NaCl, NaBr, KCl and KBr), follow a relationship derived from the pseudophase micellar (PM) model coupled with an empirical equation. This relationship gives empirical constants, F X/S and K X/S , with S … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 55 publications
0
13
0
Order By: Relevance
“…The values of K X Y have been calculated from the relationship: K X Y = K X/S n /K Y/S n for X = Brand Y = Clusing the values of K Br/S n and K Cl/S n (for MX = LiX, NaX and KX). These calculated values of K Br Cl at different [CTABr] T for M + = Li + , Na + and K + are almost independent of [CTABr] T within the range 0.006-0.016 M. The mean values of K Br Cl are 3.9 ± 0.5, 2.7 ± 0.1 and 2.6 ± 0.3 for Li + , Na + and K + respectively [67]. The values of K Br Cl (= 2.7 ± 0.1 and 2.6 ± 0.3 for M + = Na + and K + respectively) may be compared with the reported values of 2-3 [68], 2.7 [69] and 5 [70] obtained by the use of different physicochemical techniques.…”
Section: Estimation Of Ion Exchange Constants K Xmentioning
confidence: 75%
See 1 more Smart Citation
“…The values of K X Y have been calculated from the relationship: K X Y = K X/S n /K Y/S n for X = Brand Y = Clusing the values of K Br/S n and K Cl/S n (for MX = LiX, NaX and KX). These calculated values of K Br Cl at different [CTABr] T for M + = Li + , Na + and K + are almost independent of [CTABr] T within the range 0.006-0.016 M. The mean values of K Br Cl are 3.9 ± 0.5, 2.7 ± 0.1 and 2.6 ± 0.3 for Li + , Na + and K + respectively [67]. The values of K Br Cl (= 2.7 ± 0.1 and 2.6 ± 0.3 for M + = Na + and K + respectively) may be compared with the reported values of 2-3 [68], 2.7 [69] and 5 [70] obtained by the use of different physicochemical techniques.…”
Section: Estimation Of Ion Exchange Constants K Xmentioning
confidence: 75%
“…The values of K Br Cl (= 2.7 ± 0.1 and 2.6 ± 0.3 for M + = Na + and K + respectively) may be compared with the reported values of 2-3 [68], 2.7 [69] and 5 [70] obtained by the use of different physicochemical techniques. The values of K X/S or K X/S n can be determined using either semi-empirical kinetic (SEK) [5,14,31,67] or semi-empirical spectrophotometric (SESp) [71] methods. The SEK method involves kinetic measurements of an appropriate reaction probe molecule while the SESp method involves an appropriate spectrophotometric probe molecule.…”
Section: Estimation Of Ion Exchange Constants K Xmentioning
confidence: 99%
“…The plausible explanations for the value of k W /k M 22 may be the same as described elsewhere 38 for the same reaction in the presence of CTABr micelles/FNs. The value k W /k M shows that the apparent negative catalysis/inhibition of TTABr micelle/FNs is 22-fold.…”
Section: Rheological Measurementsmentioning
confidence: 84%
“…Commercially available reagent-grade chemicals such as piperidine (pip), phenyl salicylate (PheSH), HDAB, C 16 E 20 and sodium bromide (NaBr) were used as received. [19,27]. Pseudo first-order rate constants, k obs , for the piperidinolysis of PheSare affected by the amount of counterion, X -.…”
Section: Reagentsmentioning
confidence: 99%
“…In addition, some studies [13][14][15] reported possible quantitative correlations between the hexadecyltrimethylammonium bromide (HDAB) micellar binding constants and the counterion and/or temperature-induced micellar structural growth. These studies [13][14][15] and some related ones [16][17][18] used a semi-empirical kinetic (SEK) method to determine the values of the relative counterion binding constant, K X Br or R X Br (with R X Br = K X /K Br , where the values of HDAB micellar binding constants, K Br and K X , were derived from kinetic parameters obtained in the presence of micelles with different structural features) [19]. However, these reports lack information on reliable mechanism(s) of the effects of nonionic surfactants in the cationic micellar structural transition which opens up the possibility of optimising the use of mixed micelles in advanced technologies and industries [20].…”
Section: Introductionmentioning
confidence: 99%